Live imaging of mitosomes and hydrogenosomes by HaloTag technology - Martincová, Eva; Voleman, Luboš; Najdrová, Vladimíra; De Napoli, Maximiliano; Eshar, Shiri; Gualdron, Melisa; Hopp, Christine S; Sanin, David E; Tembo, Dumizulu L; Van Tyne, Daria; Walker, Dawn; Marcinčiková, Michaela; et al. (PloS one, 2012)
Hydrogenosomes and mitosomes represent remarkable mitochondrial adaptations in the anaerobic parasitic protists such as Trichomonas vaginalis and Giardia intestinalis, respectively. In order to provide a tool to study these organelles in the live cells, the HaloTag was fused to G. intestinalis IscU and T. vaginalis frataxin and expressed in the mitosomes and hydrogenosomes, respectively. The incubation of the parasites with the fluorescent Halo-ligand resulted in highly specific organellar labeling, allowing live imaging of the organelles. With the array of available ligands the HaloTag technology offers a new tool to study the dynamics of mitochondria-related compartments as well as other cellular components in these intriguing unicellular eukaryotes.
Keywords: Mitochondria; viabilita buněk; Recombinant Fusion Proteins; ligandy; reportérové geny; Ligands; Genetic Vectors; Cell Survival; anaerobióza; Hydrolases; protozoální proteiny; rekombinantní fúzní proteiny; hydrolasy; organely; Trichomonas vaginalis; Molecular Imaging; Organelles; Giardia lamblia; Anaerobiosis; genetické vektory; molekulární zobrazování; Protozoan Proteins; Genes, Reporter; mitochondrie